PENGEMBANGAN MEDIA ULAR TANGGA BUDAYA SLEMAN UNTUK PEMBELAJARAN MATEMATIKA BILANGAN BULAT DI KELAS V SEKOLAH DASAR - Purnomo , Anton; Al Masjid , Akbar (ATTA`DIB, 2024)
The lack of teacher creativity and innovation in creating learning media is one of the factors in the lack of integer mathematics learning activities in class V. The aim of the research is to describe needs analysis, development, feasibility, and testing the effectiveness of Sleman Culture’s snakes and ladders media. This research includes research and development (R&D) with research instruments in the form of validation sheets, teacher response questionnaires and student response questionnaires, observation and evaluation. The research object is SD Muh. Sangonan IV class VA (control class) with 30 student and VB (experimental class) with 28 student. Sleman’s cultural snakes and ladders media is suitable for use based on validation results by material experts with a percentage of 90.91% categorized as "very feasible" and a percentage of 91.67% from media expert validation which is also categorized as "very feasible". Product effectiveness. is calculated using the t-test with a sig value. (2 tailed) is 0.000 < 0.05, then Ho is rejected and Ha is accepted, meaning there is a significant difference in learning outcomes between the experimental class and the control class.